Measuring Behavioural and Social Drivers (BeSD) of COVID-19 Vaccination, UNICEF Application of Globally Standardized Data Collection Tools in Eastern and Southern Africa - Brouwers, S.; Bon, Helena B.; de Almeida, S. C.; Mote, J.; Sommariva, S. (VARN2022 Shaping Global Vaccine Acceptance with Localized Knowledge - Sabin Vaccine Institute, 2022)
Introduction. Twenty countries in the Eastern and Southern Africa (ESA) region have introduced COVID-19 vaccines in 2021. Understanding drivers and barriers of vaccine demand and uptake is essential for reaching and maintaining high coverage of COVID-19 vaccination. In 2018, WHO established the global working group ‘Measuring Behavioural and Social Drivers of Vaccination’ (BeSD) that included UNICEF; the US Centers for Disease Control and Prevention; Gavi, the Vaccine Alliance; and the Bill and Melinda Gates Foundation (1). Based on the “increasing vaccination” model of Brewer et al (2017), its objective was to enable programmes to systematically gather and use behavioural science data related to childhood immunization uptake . Tools were later adapted to the COVID-19 context , with qualitative and quantitative questionnaires covering four domains that increase vaccine uptake: what people think and feel about vaccines, the social processes that drive or inhibit vaccination, motivations (or hesitancy) to seek vaccination, and practical issues to get vaccinated. The tools also included targeted questionnaires for health workers. Methodology. This paper describes the main findings of the application of the COVID-19 BeSD tools for health workers via the Internet of Good Things (IoGT) from February to August 2021 in five UNICEF Country Offices (COs) in ESA: Kenya, Malawi, Mozambique, South Africa and South Sudan. Responses to four drivers of the BESD, namely Thinking & Feeling, Social Processes, Motivation, and Practical Issues, are analysed in search for patterns across demographics that can inform programmatic recommendations. Further analysis of the associations between three interconnected core drivers of the BeSD, namely Thinking & Feeling, Social Processes, and Motivation, is conducted to reveal insights on the hypothesized directionality of increases from one driver to another. Results. Findings showed that most respondents thought the vaccine was very important for their health, but under 30% would trust it very much. And while almost 66% of all respondents would take the vaccine if recommended to them, only 49% thought most adults would, and only 48% thought their co-workers would. Access was highlighted as a crucial barrier, with less than a quarter reporting that accessing vaccination services for themselves would be very easy. Responses from women highlighted slightly less trust and confidence, willingness to give a recommendation, intention to vaccinate, ease of access, and less-established descriptive social and workplace norms. The analysis also shows that Social Processes becomes the best predictor of Motivation when programme designers create unique age-specific interventions for Thinking & Feeling. Conclusions. The BeSD package offers standardized data collection tools and indicators to measure drivers of vaccine demand and uptake. (2) However, realizing the full benefits of these tools requires Government buy-in for ownership of and action driven by the results. On a larger scale, investment is needed to strengthen the sustainability of systematic collection and monitoring of social and behavioural time-series, disaggregated data, especially considering the lack of standardized government-led monitoring systems in this area. Findings were used to inform the design of targeted interventions, suggest programmatic recommendations to Governments and implementing partners, evaluate trends over time, and for advocacy purposes. https://www.varnconference.org/wp-content/uploads/2022/02/Helena-Ballester-Bon-presentation.pdf